Conocimiento sobre tuberculosis y actitud hacia el tratamiento en pacientes atendidos en el establecimiento de salud Morona Cocha Iquitos 2022 - Rengifo Padilla, Allison Elaene (2023)
The purpose was to determine the relationship between knowledge about Pulmonary Tuberculosis and attitude towards treatment in patients treated in the Health Strategy for Prevention and Control of Tuberculosis, establishment of health I-4 Morona Cocha, Iquitos. It is a quantitative, non-experimental, descriptive, cross-sectional and correlational study; whose population consisted of 72 patients, diagnosed with TB. The technique used was the survey, the instruments were the knowledge questionnaire on Tuberculosis (Validity 80.0% and reliability 80.0%) and Likert scale (validity 95.0% and reliability 88.4%). The results obtained were: mean age (36.69 years) with SD ±16.6 years; 61.1% (44) were male and 38.9% (28) female; 56.9% (41) single and 34.7% (25) cohabiting; independent occupancy 54.2% (39), housewives 25.0% (18) and dependents 20.8% (15); 68.1% (49) are Catholic and 27.8% (20) are evangelical. Regarding knowledge about Tuberculosis, 80.6% (58) presented high knowledge, 19.4% (14) medium and 0% (0) low; 83.3% (60) showed acceptance towards treatment, 16.7% (12) indifference and 0% (0) rejection. In conclusion, there is significance between knowledge about tuberculosis and attitude towards antituberculous treatment (p = 0.003; p < 0.05), in patients of IPRESS I-4 Morona Cocha, from Iquitos.